Building Italian Regional Identity in Toronto: Using Space to Make Culture Material - Harney, Nicholas (Anthropologica, 2022)
The landscape of greater Toronto is dotted with Italian ethnoregional community centres constructed with financial and diplomatic help from Italian regional governments. These ethnoregional centres are physical representations of Italian Canadianness and used by Italian Canadians to create meaningful spaces, to generate collective sentiment and locate themselves in the land of immigration. The ethnographic examples used in this paper, I suggest, require us to consider how to locate the ideas of flow and deterritorialization in recent anthropological work through local realities. Italian immigrants and their descendants participate in diasporic discourses and practices to construct physical places of identification to make their sentiment material and reterritorialize their identity. Further, these sites shed light on the way states alter their activities to adapt to the movement of people, money and ideas across borders. The Italian national and regional governments and levels of the Canadian state respond to the challenges of transnationality by practicing a kind of governmentality, a "flexible sovereignty" through the support of these projects. As such these projects help to organize the behaviour and identity of Italians living overseas.